An Assessment of the 2023 Presidential Election in Nigeria: A Study of Kwara State (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2023)
The paper examines the 2023 presidential election in Nigeria: a study of Kwara state. This paper is a case study research work. To this end, the Kwara State election is a study and an analysis of its impact on the concluded presidential election in Nigeria. The unchangeable conventional political analysis has repeated itself in Nigerian politics; as the north central zone has been one of the determinants of winning the presidential election since the inception of the fourth republic, the tradition remains unchanged. Kwara State, as one of the states in north central, cannot be ignored from this historical legacy. This research aims to analyze the presidential election in Kwara State with in-depth analysis from an electoral behaviour perspective. The theory employed in this work is a voting theory that is more beneficial to this paperwork. The research methodology comprises primary data from key informant interviews of Independent National Electoral Commission (INEC) officials, party agents, and electorates; the secondary data include texts, journals, television media, and newspapers. The findings revealed the APC candidate as the winner of the presidential election. Likewise, the research identified the Bimodal Voter Accreditation System (BVAS) flaws and its causes. One of the prime recommendations is the need to improve the technology rate of Nigeria's electronic voting system in terms of service and technical know-how.